Studying Student Experience of Technology Enhanced Assessment Methods (TEAM) in Science and Health in Ireland. (10th January 2018) - Kavanagh, Yvonne; Brazil, Dina; Noonan, Gina; Dowling, David; Bree, Ronan; Healy, Edel; Maguire, Moira; Faller, Don; Harding, Nuala; Mulvihill, Ann; Akande, Akinlolu; Doyle, David; et al.
ABSTRACT: This is a cross institution project involving four Institutes of Technology in Ireland. The objective of this project is to assess the use of technology to enhance the assessment of laboratory sessions in Science and Health. In science, health and engineering, the laboratory sessions are at the core of the learning process for skill development. These laboratory sessions focus on the skills acquisition. The Irish Institute of Technology sector, in particular, develops these skills and considers them essential for 'professionally ready' graduates. In terms of student progression and retention, the assessment structure has been identified as having a significant impact on student engagement. The Technology Enhanced Assessment Methods (TEAM) project led by Dundalk Institute of Technology and partnering with Institute of Technology Sligo, Athlone Institute of Technology and Institute of Technology Carlow is exploring the potential offered by digital technologies to address these concerns. It aims to develop a framework for applying the principles of effective assessment and feedback to practical assessment. The TEAM project also aims to facilitate dialogue among stakeholders about what it is we want student to learn in laboratory sessions and how our assessment can facilitate this. A peer network of discipline-specific academics and students in the Science and Health field has been established across all four Institutes. As the network focuses on authentic skills assessment in all core modules, including physics and chemistry, the best practice from this project will inform future assessment procedures across laboratory sessions and may be considered for application within a Science and Materials Engineering context. Assessing the skills acquired in this environment takes many forms. Using student and stakeholder feedback along with an extensive literature review of the area, the team identified key technologies that cut across science and health disciplines, with the potential to influence and enable the learning process. The emphasis was on developing a powerful learning environment approach to enable students to deepen their learning through engagement with the process. The areas identified are: (i) Pre-practical preparation (videos and quizzes), (ii) Electronic laboratory notebooks and ePortfolios, (iii) Digital Feedback technologies and (iv) Rubrics). This paper describes the student experience and perceptions of the adoption of digital technology in science practical assessments. It also describes the process involved in setting up the pilot structure and it presents the initial results from the student survey.